2021
DOI: 10.3390/tropicalmed6020105
|View full text |Cite
|
Sign up to set email alerts
|

Extended Spectrum Beta-Lactamase Escherichia coli in River Waters Collected from Two Cities in Ghana, 2018–2020

Abstract: Infections by Extended-Spectrum Beta-Lactamase producing Escherichia coli (ESBL-Ec) are on the increase in Ghana, but the level of environmental contamination with this organism, which may contribute to growing Antimicrobial Resistance (AMR), is unknown. Using the WHO OneHealth Tricycle Protocol, we investigated the contamination of E. coli (Ec) and ESBL-Ec in two rivers in Ghana (Odaw in Accra and Okurudu in Kasoa) that receive effluents from human and animal wastewater hotspots over a 12-month period. Concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…The site with the highest prevalence of ESBL-producing E. coli was located downstream of a treated effluent outlet (site F). This is not surprising as it has previously been shown that wastewater treatment is not completely effective at removing antimicrobial resistant bacteria [59][60][61][62], and studies have found a higher prevalence of ESBL-producing E. coli and other types of resistant E. coli immediately downstream of effluent outlets [32,[63][64][65]. A higher prevalence of antimicrobial resistant bacteria and their genes has also been detected during periods associated with higher rainfall [66][67][68].…”
Section: Discussionmentioning
confidence: 93%
“…The site with the highest prevalence of ESBL-producing E. coli was located downstream of a treated effluent outlet (site F). This is not surprising as it has previously been shown that wastewater treatment is not completely effective at removing antimicrobial resistant bacteria [59][60][61][62], and studies have found a higher prevalence of ESBL-producing E. coli and other types of resistant E. coli immediately downstream of effluent outlets [32,[63][64][65]. A higher prevalence of antimicrobial resistant bacteria and their genes has also been detected during periods associated with higher rainfall [66][67][68].…”
Section: Discussionmentioning
confidence: 93%
“…Such a monitoring system would provide early signals of emergent AMR threats, and background data against which the impact of MDA programs and AMR mitigation efforts can be assessed. Existing wastewater surveillance systems for polio or COVID-19 can provide a starting point [ 127 , 128 ] possibly building on the World Health Organization Tricycle Protocol [ 129 ] that focuses on ESBL E. coli monitoring in environmental matrices [ 130 ]. This protocol has been designed specifically for cost-effective, at-scale AMR monitoring in LMICs.…”
Section: Strategies For Mitigation Of Amr Following Mdamentioning
confidence: 99%
“…Several reports from Ghana show increasing AMR, with a high prevalence of resistance phenotypes such as extended-spectrum beta-lactamases and increasing reports of carbapenemase-producing bacteria. 4–7 The Ghana national policy and action plan on AMR that is aligned with the global action plan on AMR highlight the need to strengthen surveillance and research as well as optimize the use of antimicrobials. 8 Optimizing antimicrobial use and consumption through antimicrobial stewardship hinges on the availability of antimicrobial use and consumption data.…”
Section: Introductionmentioning
confidence: 99%